The Hands of the Blacks Racism and Myths of Origin - Topa, Francisco (Africana Studia, 2022)
This paper discusses some mythical accounts from different sources about skin colour, using as a starting point the short story “As mãos dos pretos” [The hands of the blacks] by the Mozambican author Luís Bernardo Honwana. It was published in book form in 1964, a previous version having been issued in a newspaper. Keywords: racism, myths of origin, Mozambique, Luís Bernardo Honwana.